SPIRITUAL ACUITY AS A RESULT OF THE INTEGRATION OF CHRISTIAN EDUCATION AND SPIRITUALITY: A DESCRIPTIVE STUDY OF THE FORMATION OF CHRIST'S MESSENGERS IN THE POSTMODERN ERA - GP, Harianto (Sekolah Tinggi Agama Kristen Anak Bangsa, 2025)
Pendidikan Kristen di era postmodern menghadapi tantangan serius akibat globalisasi, relativisme nilai, dan digitalisasi budaya yang kerap melemahkan integritas iman generasi muda. Penelitian ini bertujuan mengkaji bagaimana ketajaman rohani, sebagai kepekaan utusan Kristus dalam membedakan kehendak Allah, dapat dibentuk melalui integrasi pendidikan Kristen dan spiritualitas. Dengan pendekatan kualitatif deskriptif, data dikumpulkan melalui studi literatur, observasi program, wawancara guru, dan analisis dokumen di sekolah teologi Kristen wilayah Jabodetabek. Hasil penelitian menemukan lima persoalan utama: belum adanya indikator sistematis untuk menilai spiritualitas siswa, kurikulum yang kurang mengintegrasikan iman, dominasi pembelajaran kognitif tanpa transformasi spiritual, minimnya evaluasi rohani berkelanjutan, serta terbatasnya model pembentukan rohani yang relevan di era digital. Untuk menjawab tantangan ini, penelitian menawarkan kerangka kerja terpadu yang meliputi kurikulum holistik, praktik spiritual terarah (retret, mentoring, pelayanan), dan evaluasi longitudinal. Kontribusi studi ini terletak pada pengembangan model pendidikan Kristen yang kontekstual serta penekanan pada formasi spiritual yang menyatu dalam seluruh proses belajar. Implikasi penelitian menunjukkan perlunya reformasi kurikulum dan peningkatan pelatihan guru guna memperkuat ketajaman rohani siswa, serta mendorong penelitian empiris lanjutan untuk menguji efektivitas model yang diajukan.Christian education in the postmodern era faces significant challenges from globalization, value relativism, and cultural digitalization, which often weaken the faith integrity of young generations. This study aims to explore how spiritual acuity, understood as the sensitivity of Christ's messengers to discern God's will, can be shaped through the integration of Christian education and spirituality. Using a descriptive qualitative approach, data were collected through literature review, program observation, teacher interviews, and document analysis in Christian theological high schools in the Greater Jakarta area. The findings reveal five major issues: the absence of systematic indicators to assess students' spirituality, a curriculum that lacks full faith integration, the dominance of cognitive learning without spiritual transformation, limited continuous evaluation of spirituality, and the scarcity of contextual spiritual formation models relevant to the digital era. To address these challenges, the study proposes an integrated framework consisting of a holistic curriculum, directed spiritual practices (retreats, mentoring, ministry), and longitudinal evaluation. The contribution of this research lies in developing a contextual model of Christian education that emphasizes spiritual formation as an inseparable part of the learning process. The implications highlight the need for curriculum reform and systematic teacher training to strengthen students' spiritual acuity, while further empirical studies are recommended to test the effectiveness of the proposed model